Impact of Perceived Service Quality on Customer Loyalty in Restaurant Industry of Birendranagar, Surkhet: Mediating Role of Customer Satisfaction and Word-of-Mouth - K.C. , Govinda (Journal of Entrepreneurship & Management Studies, 2025)
This study is about restaurant industry of Birendranagar, Surkhet. The purpose of this study is to see how perceived service quality influences the customer loyalty directly and indirectly through customer satisfaction and positive word-of-mouth. Because of changing customer behavior, influence regarding social media and exposure to outer world competition has intensified in all business including hospitality sector.  There are four constructs: perceived product quality, customer satisfaction positive word-of-mouth and customer fidelity in this research. Structured questionnaire was designed focusing on four construct to collect primary data from restaurant customers. The study employs quantitative analysis techniques, including structural equation modeling, to examine the relationships among constructs.The findings are expected to reveal that high service quality significantly enhances customer satisfaction and fosters positive word-of-mouth, both of which contribute to strengthening customer loyalty. This research provides practical implications for restaurant managers seeking to enhance customer retention and build sustainable brand relationships in a growing regional market.